2022
DOI: 10.1186/s12991-022-00400-7
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety in different hypertension phenotypes: a cross-sectional study

Abstract: Background Hypertension is a major risk factor of cardiovascular mortality. Mood disorders represent a growing public health problem worldwide. A complex relationship is present between mood disorders and cardiovascular diseases. However, less data is available about the level of depression and anxiety in different hypertension phenotypes. The aim of our study was to evaluate psychometric parameters in healthy controls (Cont), in patients with white-coat hypertension (WhHT), with chronic, non-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Previous studies reported the association of WCHT with depression, anxiety, mental stress, and introverted personality traits [ 9 , 10 , 12 , 29 ]. Nonetheless, few studies have evaluated the association between MHT and depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported the association of WCHT with depression, anxiety, mental stress, and introverted personality traits [ 9 , 10 , 12 , 29 ]. Nonetheless, few studies have evaluated the association between MHT and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Mental status, including depression, anxiety, stress, and personality, reportedly could influence BP [ 9 13 ]. However, the association between MHT and depression remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers indicated that the neurovascular manifestations show an age-related penetrance with an increased prevalence of cerebral manifestations over the lifespan [ 41 , 45 ]. A large number of patients suffering from HHT are able to identify one or more traumatic events related to their disease that caused psychological distress; therefore, the longer they live and the more bleeding episodes they experience, the more mentally affected they may be [ 47 , 54 , 55 , 56 , 57 , 58 , 59 ]. Our patient has a long history of hypertension and a poor therapy adherence; therefore, the causality connection between high blood pressure and anxiety, depression, or even an evolution towards dementia cannot be excluded [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%